Penggunaan nanoenkapsulasi ekstrak buah mahkota dewa (Phaleria macrocarpa) dalam air minum terhadap performa produksi ayam broiler - Niati Ningsih; Bambang Ariyadi; Zuprizal Zuprizal (Jurnal Ilmu Peternakan Terapan, 2021)
The purpose of this study was to investigate the use of nanoencapsulation of Phaleria macrocarpa fruits extract (NEPM) in drinking water and the effect on broiler growth performance. A total number of 200 male broiler chicks, aged eight days old, were distributed into 5 treatments with 4 replicates (10 birds in each replicate). The experimental treatments consisted of the basal diet (P0; negative control), and basal diet with antibiotic tetracycline supplementation (P1; positive control), and basal diets with 2.5% of Phaleria macrocarpa fruits extract (P2), 2.5% NEPM (P3), or 5.0% NEPM (P4). The basal diet was based on yellow corn and soybean meal that contains 20.44% crude protein, 2917.47 kcal/kg metabolizable energy, 0.84% Calcium, and 0.51% available Phosphorus. The diets and drinking water was supplied for ad libitum consumption. Parameters evaluated in the current study were growth performance (feed consumption and conversation, body weight gain, water consumption, slaughter and carcass weight, and carcass percentage), Data were analyzed using analysis of variance in a completely randomized design. Orthogonal contrast tests were used to separate data with a significant difference. Results showed that supplementation of NEPM in the drinking water did not affect growth performance of broiler chicken.